CREATING AN ADDITIONAL DEVICE TO ACCELERATE THE OUTPUT OF SEED FROM THE WORKING CHAMBER OF THE 5DP-130 SAW (Journal of Science-Innovative Research in Uzbekistan, 2024)
This study aims to improve the efficiency of seed output from the working chamber of the 5DP-130 saw by designing and implementing an auxiliary acceleration device. Efficient seed extraction is critical for agricultural productivity, and this project seeks to optimize the process by augmenting the saw with an additional mechanism. Through careful consideration of design factors such as mechanism selection, integration with the saw, compatibility with different seed types, and efficiency and safety measures, the goal is to enhance overall operational efficiency and throughput. This research contributes to advancements in agricultural processing technology, offering a practical solution to streamline seed extraction in the 5DP-130 saw. In this article, we made changes to the seed comb of the 5DP-130 chainsaw genie. In this case, we can increase the productivity of the gin equipment and seed output to a certain extent, and it also allows us to control the density of raw materials